Experiences matter: Educators’ attitudes toward disability in higher education - Freer, John; Kaefer, Tanya (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
This study investigated 128 post-secondary educators’ attitudes toward disability at a college and a university in southwestern Ontario, Canada. The participants completed the Educators’ Attitudes toward Disability Scale (EADS) and a demographic questionnaire that included questions about their experiences with disability. There were three research questions at the heart of this study: (1) What are post-secondary educators’ overall attitudes toward disability? (2) Do demographic factors predict post-secondary educators’ attitudes toward disability? (3) Does exposure to people with disability predict post-secondary educators’ attitudes toward disability? The findings of this study suggest post-secondary educators hold overallpositive attitudes toward disability and there were very few differences observed between groups (e.g., based on age, gender, discipline, etc.). Educators’ experiences with people who have a disability, however, were positively associated with their attitudes. This factor included personal experiences (e.g., friends, family, etc.), but also professional experiences (e.g., students in their classes).